Women's Representation In The Korea Drama "It's Okay, That's Love" (Semiotics Analysis Study) (International Journal of Cultural and Social Science, 2022)
The purpose of this study is to find out how the representation of women in the Korean drama it's okay thats loved and find the meanings and signs used to solve this research is the theory of semiotics. The object of the research is the Korean drama it's okay thats love, which is a drama produced by South Korea and aired in 2014 consisting of 16 episodes with a duration of 59-60 minutes. The method used in this study is a qualitative method with the semiotic analysis technique of the Roland Barthes model. The results of the study show that there are several scenes that depict the representation of women in the Korean drama it's okay thats love. The representation of women can be seen from the signs and meanings studied through Roland Barthes' semiotic theory.